The cost‐effectiveness of isavuconazole compared to voriconazole, the standard of care in the treatment of patients with invasive mould diseases, prior to differential pathogen diagnosis in Spain. Issue 1 (30th October 2020) - Azanza, José Ramón; Grau, Santiago; Vázquez, Lourdes; Rebollo, Pablo; Peral, Carmen; López‐Ibáñez de Aldecoa, Alejandra; López‐Gómez, Vanessa
Abstract: Background: Invasive mould diseases are associated with high morbidity, mortality and economic impact. Its treatment is often started prior to differential pathogen diagnosis. Isavuconazole is approved for treatment of invasive aspergillosis (IA) and invasive mucormycosis (IM) when amphotericin‐B is not indicated. Objectives: To estimate the cost‐effectiveness of isavuconazole vs voriconazole for the treatment of adult patients with possible IA prior to differential pathogen diagnosis, in Spain. Methods: A decision tree analysis was performed using the Spanish Healthcare System perspective. Among all patients with possible IA, it was considered that 7.81% actually had IM. Costs for laboratory analysis, management of adverse events, hospitalisation and drugs per patient, deaths and long‐term effects in life years (LYs) and quality‐adjusted LYs (QALYs) were considered. Efficacy data were obtained from clinical trials and utilities from the literature. Deterministic and probabilistic sensitivity analyses (PSA) were conducted. Results: In patients with possible IA and when compared to voricanozole, isavuconazole showed an incremental cost of 4758.53€, besides an incremental effectiveness of +0.49 LYs and +0.41 QALYs per patient. The Incremental Cost Effectiveness Ratio was 9622.52€ per LY gained and 11, 734.79€ per QALY gained. The higher cost of isavuconazole was due to drug acquisition. Main parameters influencing results were mortality, treatment duration and hospitalisation days. The PSA results showed that isavuconazole has a probability of being cost‐effective of 67.34%, being dominant in 24.00% of cases. Conclusions: Isavuconazole is a cost‐effective treatment compared to voriconazole for patients with possible IA for a willingness to pay threshold of 25, 000€ per additional QALY.